Sensory quality and consumers’ acceptance towards wild and farmed brown-trout (Salmo trutta) and farmed rainbow-trout (Oncorhynchus mykiss) - Geraldes, Ana Maria (2020)
The present study aims to compare the sensory qualities and the degree of acceptance of wild/farmed brown-trout (Salmo trutta) and the farmed rainbow-trout (Onchorynchus mykiss) by a consumer panel. Acceptability regarding attributes appearance, taste, texture, and global appreciation were evaluated on 20 wild brown-trout, 20 farmed brown-trout and 20 farmed rainbow trout by a consumers’ panel formed by 74 elements. Although the panel of consumers equally well accepted all samples, the rainbow trout had classifications slightly higher in all sensory attributes. This tendency was confirmed by internal preference maps performed for each studied attribute. Consumers’ slightly higher preference for farmed fish might indicate that farmed trout could be an alternative to wild brown trout.